Comorbidities and recurrence of benign paroxysmal positional vertigo: personal experience. (3rd May 2016) - Picciotti, P. M.; Lucidi, D.; De Corso, E.; Meucci, D.; Sergi, B.; Paludetti, G.
Abstract: Objective : The aim of this study is to evaluate the correlation between clinical features of benign paroxysmal positional vertigo (BPPV) and age, sex, trauma, presence of one or more comorbidities such as cardiovascular, neurological, endocrinological, metabolic, psychiatric diseases. Design: Retrospective review of medical records (chart review). Study sample : A total of 475 patients aged from 14 to 87 years, affected by BPPV. Results : Recurrence of BPPV occurred in 139/475 patients (29.2%). The recurrence rate was significantly higher in female and older patients. Comorbidities were present in 72.6% of subjects with recurrent BPPV vs. 48.9% of patients with no recurrence (p <0.01). Forty-two patients (8.8%) reported a cranial trauma as a triggering event. Post-traumatic patients showed a significantly higher persistence rate (45.2%) compared to patients affected by non-traumatic BPPV (20.5%). Recurrence rates are overlapping between the two groups. Conclusion : Our results confirm the association between recurrence of BPPV and age, female sex, and presence of comorbidities. The correlation is stronger in patients affected by multiple associated diseases; the most frequently involved pathologies are psychiatric disorders, followed by neurological and vascular diseases. Collecting a complete medical history is important for prognostic stratification and detection of potential underlying pathological conditions.